ChemInform Abstract: Multicomponent Synthesis of Diverse 1, 4‐Benzodiazepine Scaffolds. Issue 17 (4th April 2013) - Huang, Yijun; Khoury, Kareem; Chanas, Tyler; Doemling, Alexander
Abstract Entitled 1, 4‐benzodiazepines are of particular interest in drug design.